A Comprehensive Pathological Survey of Duodenal Biopsies from Dogs with Diet‐Responsive Chronic Enteropathy. (10th May 2013) - Walker, D.; Knuchel‐Takano, A.; McCutchan, A.; Chang, Y‐M.; Downes, C.; Miller, S.; Stevens, K.; Verheyen, K.; Phillips, A.D.; Miah, S.; Turmaine, M.; Hibbert, A.; et al.
<x xml:space="preserve">Abstract</x> Background The detailed pathological phenotype of diet‐responsive chronic enteropathy (CE) and its modulation with dietary therapy remain poorly characterized. Hypothesis/Objectives Key mucosal lesions of diet‐responsive CE resolve with dietary therapy. Methods This was a prospective observational study of 20 dogs with diet‐responsive CE. Endoscopic duodenal biopsies collected before and 6 weeks after the start of a dietary trial were assessed by means of qualitative and quantitative histopathological, immunohistochemical, and ultrastructural criteria. Control duodenal biopsies were obtained from 10 healthy Beagle dogs on 1 occasion. Results Compared with control dogs, the CE dogs had higher villus stunting scores and higher overall WSAVA scores, a lower villus height‐to‐width ratio, and higher lamina propria density of eosinophils. The CE dogs also had ultrastructural lesions of the mitochondria and brush border. In common with other studies in which the disease and control populations are not matched for breed, age, sex, and environment, these comparisons should be interpreted with caution. Comparing biopsies collected at presentation and 6 weeks after starting the dietary trial, mean lamina propria mononuclear cell score and lamina propria densities of eosinophils and mononuclear cells decreased. Dietary therapy also improved ultrastructural lesions of the mitochondria and brush border, eliciting a decrease in intermicrovillar space and an increase in microvillus height. Conclusions and Clinical Importance In dogs with diet‐responsive CE, the remission of clinical signs with dietary therapy is associated with subtle decreases in lamina propria density of eosinophils and mononuclear cells, and resolution of ultrastructural lesions of the enterocyte.